1995
DOI: 10.1002/qua.560550405
|View full text |Cite
|
Sign up to set email alerts
|

Total energy calculations in the DFT on binary compounds

Abstract: Calculations are carried out using first-principles self-consistent local-density and nonlocal density theory of the electronic structure, the total energy, and the charge density of a variety of semiconducting and insulating compounds under hydrostatic and uniaxial pressure. For several cases, the transition pressure from one structure to another is determined as well as the pressure coefficients of the main band gaps. It is shown that several properties are calculated with adequate accuracy to be compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…With this in mind a study of MgTe and MgSe was begun. It was found that at atmospheric pressure MgTe existed both as the wurzite and nickel arsenide structure and that the B8, NiAs, phase was the more stable, and persisted at high pressure [4], consistent with calculations [5,6]. In the ideal B8 phase of MgTe, the magnesium atom is surrounded by eight equidistant atoms, six tellurium atoms and two magnesium atoms , while the tellurium is surrounded by six equidistant atoms of magnesium.…”
supporting
confidence: 71%
“…With this in mind a study of MgTe and MgSe was begun. It was found that at atmospheric pressure MgTe existed both as the wurzite and nickel arsenide structure and that the B8, NiAs, phase was the more stable, and persisted at high pressure [4], consistent with calculations [5,6]. In the ideal B8 phase of MgTe, the magnesium atom is surrounded by eight equidistant atoms, six tellurium atoms and two magnesium atoms , while the tellurium is surrounded by six equidistant atoms of magnesium.…”
supporting
confidence: 71%
“…[18] microscopic point of view. The calculated equilibrium lattice constants a, elastic constants C ij , zero-pressure bulk modulus B 0 and its pressure derivation B 0 from the Birch-Murnaghan equation of state (EOS) [17] are listed in Table 1, together with other theoretical results [5][6][7][18][19][20][21][22][23][24][25][26][27]4] and the experimental data [28]. The agreements among them are good.…”
Section: Resultsmentioning
confidence: 94%
“…These calculations are therefore used to investigate the structures of materials at high pressures. The significant advances in computational materials science have made possible the use of ab initio quantum mechanical techniques to predict MgTe the electronic structure [3,6], the phase transition [4,5] and optical properties [7]. Such studies could play a significant role from the standpoint of predicting the performance of the material under extreme conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated values of SOECs, bulk modulus B T and tetragonal modulus C S are given in Table 4 and are also compared with others works [4,9,12,20,25,[27][28][29][30][31][32][33][34]. Vukcevich [35] proposed a high-pressure stability criterion for ionic crystals, combining mechanical stability with minimum energy conditions.…”
Section: Article In Pressmentioning
confidence: 97%